2019
DOI: 10.3847/1538-4357/ab3c58
|View full text |Cite
|
Sign up to set email alerts
|

Radio Spectroscopic Imaging of a Solar Flare Termination Shock: Split-band Feature as Evidence for Shock Compression

Abstract: Solar flare termination shocks have been suggested as one of the promising drivers for particle acceleration in solar flares, yet observational evidence remains rare. By utilizing radio dynamic spectroscopic imaging of decimetric stochastic spike bursts in an eruptive flare, Chen et al. found that the bursts form a dynamic surface-like feature located at the ending points of fast plasma downflows above the looptop, interpreted as a flare termination shock. One piece of observational evidence that strongly supp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 90 publications
(133 reference statements)
4
24
0
Order By: Relevance
“…The flare TS was often invoked in the standard flare model to explain the looptop HXR source (Masuda et al 1994;Shibata et al 1995;Magara et al 1996), and both theoretical and numerical models showed that the TS can be a promising candidate of acceleration mechanism (Tsuneta & Naito 1998;Mann et al 2009;Warmuth et al 2009;Guo & Giacalone 2012;Kong et al 2013;Li et al 2013). The flare TS has long been predicted in numerical magnetohydrodynamic (MHD) simulations (e.g., Forbes 1986;Magara et al 1996;Yokoyama & Shibata 1998;Takasao et al 2015;Takasao & Shibata 2016;Shen et al 2018;Cai et al 2019;Ruan et al 2020;Wang et al 2021), and observational evidence for the existence of a TS in multiple wavelengths has also been reported (e.g., Masuda et al 1994;Aurass et al 2002;Aurass & Mann 2004;Mann et al 2009;Warmuth et al 2009;Chen et al 2015Chen et al , 2019Polito et al 2018;Cai et al 2019;Luo et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The flare TS was often invoked in the standard flare model to explain the looptop HXR source (Masuda et al 1994;Shibata et al 1995;Magara et al 1996), and both theoretical and numerical models showed that the TS can be a promising candidate of acceleration mechanism (Tsuneta & Naito 1998;Mann et al 2009;Warmuth et al 2009;Guo & Giacalone 2012;Kong et al 2013;Li et al 2013). The flare TS has long been predicted in numerical magnetohydrodynamic (MHD) simulations (e.g., Forbes 1986;Magara et al 1996;Yokoyama & Shibata 1998;Takasao et al 2015;Takasao & Shibata 2016;Shen et al 2018;Cai et al 2019;Ruan et al 2020;Wang et al 2021), and observational evidence for the existence of a TS in multiple wavelengths has also been reported (e.g., Masuda et al 1994;Aurass et al 2002;Aurass & Mann 2004;Mann et al 2009;Warmuth et al 2009;Chen et al 2015Chen et al , 2019Polito et al 2018;Cai et al 2019;Luo et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among others, shocks are believed to be an important cal experiments (Forbes & Malherbe 1986;Forbes 1986Forbes , 1988Seaton & Forbes 2009;Workman et al 2011;Chen et al 2015;Takasao et al 2015;Takasao & Shibata 2016;Takahashi et al 2017;Shen et al 2018;Cai et al 2019), and have been frequently depicted in schematics of the standard solar flare model (Masuda et al 1994;Shibata et al 1995;Magara et al 1996;Forbes & Acton 1996;Lin & Forbes 2000), observational evidence for these shocks remains relatively rare. There have been only a handful of reports on possible signatures of flare termination shocks at radio, ultraviolet, and X-ray wavelengths (Masuda et al 1994;Aurass et al 2002;Aurass & Mann 2004;Mann et al 2009;Warmuth et al 2009;Chen et al 2015Chen et al , 2019Guo et al 2017;Polito et al 2018;Cai et al 2019;Tan et al 2019;Fomichev & Chernov 2020). Here we refer interested readers to Chen et al (2019) and references therein for more in-depth discussions regarding observational signatures of flare termination shocks, as well as possible reasons for the scarcity of these observations.…”
Section: Introductionmentioning
confidence: 99%
“…There have been only a handful of reports on possible signatures of flare termination shocks at radio, ultraviolet, and X-ray wavelengths (Masuda et al 1994;Aurass et al 2002;Aurass & Mann 2004;Mann et al 2009;Warmuth et al 2009;Chen et al 2015Chen et al , 2019Guo et al 2017;Polito et al 2018;Cai et al 2019;Tan et al 2019;Fomichev & Chernov 2020). Here we refer interested readers to Chen et al (2019) and references therein for more in-depth discussions regarding observational signatures of flare termination shocks, as well as possible reasons for the scarcity of these observations.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of authors found such emissions to originate from a different, secondary acceleration site (e.g. Battaglia & Benz 2009;Benz et al 2011;Carley et al 2016;Chen et al 2015Chen et al , 2019. Large solar flares usually have a long duration (up to several hours) and often display a complex morphology with multiple loop systems, hence it is not surprising that multiple acceleration sites are found.…”
Section: Introductionmentioning
confidence: 99%